#ISIS vs #ActionCountersTerrorism: a computational analysis of extremist and counter-extremist Twitter narratives - Zahrah, F; Nurse, JRC; Goldsmith, M (IEEE, 2020)
The rapid expansion of cyberspace has greatly facilitated the strategic shift of traditional crimes to on- line platforms. This has included malicious actors, such as extremist organisations, making use of online networks to disseminate propaganda and incite violence through rad- icalising individuals. In this article, we seek to advance current research by exploring how supporters of extremist organisations craft and disseminate their content, and how posts from counter-extremism agencies compare to them. In particular, this study will apply computational tech- niques to analyse the narratives of various pro-extremist and counter-extremist Twitter accounts, and investigate how the psychological motivation behind the messages compares between pro-ISIS and counter-extremism narratives. Our findings show that pro-extremist accounts often use differ- ent strategies to disseminate content (such as the types of hashtags used) when compared to counter-extremist accounts across different types of organisations, including accounts of governments and NGOs. Through this study, we provide unique insights into both extremist and counter-extremist narratives on social media platforms. Furthermore, we define several avenues for discussion regarding the extent to which counter-messaging may be effective at diminishing the online influence of extremist and other criminal organisations.